Optimalisasi Strategi Bisnis dengan Pendekatan Enterprise Resource Planning (ERP) pada PT. Citra Media Prima - Muhammad Rijal Alim Rahmat; Ridwan Andi Mattoliang; Rahmat Burhamzah; Anang Setiawan; M. Yunasri Ridhoh (Jurnal Kemitraan Masyarakat, 2024)
The Community Service (PKM) activity aimed to enhance the understanding of Enterprise Resource Planning (ERP) concepts for PT. Citra Prima Media, a provider of internet and TV services. ERP is an integrated system designed to improve operational efficiency and real-time data-driven decision-making. The method involved workshops, pre-tests, and post-tests to evaluate participants’ comprehension of ERP benefits in three key areas: financial management, marketing, and human resources (HR). The results showed significant improvements in participants’ understanding, with an average post-test score of 93%. Participants recognized ERP's role in operational efficiency, customer analytics, and data-driven HR management. Based on these findings, PT. Citra Prima Media plans to evaluate ERP adoption for a phased digital transformation. This initiative highlights the importance of ERP in supporting companies' competitiveness in the digital era.